Intertextuality in Selected Narrative Poems of Adébáyọ̀ Fálétí - Arinpe Adejumo; Adefemi Akinseloyin (Yoruba Studies Review)
The creative works of Adébáyọ Fálétí, a renowned literary writer in Yorùbá, ̀ have been the focus of literary critics. Notable among such are Olatunji (1982a; 1982b; 1982c), Ogunsina (1991), Ìṣọ̀lá (1998) and Adebowale (1999). These scholars have examined the issues of form, style and theme in Fálétí’s poetry. It has been established that Fálétí is a philosophical poet influenced by the historical, political, social and cultural contexts of the society that produced his poems. According to Olatunji (1982), “the oral poetic tradition of the Yorùbá constitutes the weft and woof of Fálétí’s poetic genius.” This attests to the claim that “no artist creates in a vacuum” (Agyekum, 2007:31). It could be deduced from the above position that there is an interplay between the text of Fálétí’s poetry and the context that produced it. Using intertextuality approach, this paper, therefore, examines the interplay of the text, context and the writer in selected poems of Adébáyọ̀ Fálétí with a view to determining the correlation between the Yorùbá oral poetic genres and the written form in Fálétí’s poetry and determining the continuity of the oral poetic genre in the written form. Fálétí’s biography has been discussed by Olatunji (1982). He was born at Agbóóyè in Ọyọ̀ ́ and had his elementary life on the farm, where he was exposed to the Yorùbá culture undiluted. He was a novelist, playwright, poet, scriptwriter and actor when alive. His works include Ọmọ Olókùn Ẹṣin, Thunderbolt, Baṣọrun Gáà, Fẹrẹ bí Ẹkùn, ̀ and Ogún Àwítẹ́lẹ. Fálétí’s works ̀ are greatly influenced by his family background because his father was a 120 Arinpe Adejumo and Adefemi Akinseloyin prominent member of the sàkàrá calabash beating oral poets and entertainers under Olatunji Kúdẹẹ̀ ̀fù in the court of Ọba Ṣiyanbọ́lá Oníkẹẹ̀ pé Ládìg ́ - bòlù I, the Aláàfin of Ọyọ̀ (1911-1944). Fálétí learnt a lot about narratives and ́ other techniques of rendition from his father’s poetic influence. There are also cases of intertextuality in his narrative poems and other literary works. Fálétí’s narrations and literary works are inspired by the tales he heard from his father, aunt and members of the larger family (Olatunji 1982). These influenced his narrative poems, as they reflect chronicles, heroism and expositions, which he borrowed from the Yorùbá oral poetic genre. Since oral poets are imbued with repertoires of praise poetry, legends, myths, proverbs, songs and history, Fálétí’s narrative poems are filled with the intertextuality of Yorùbá oral materials.